Analisis Pola Asuh Orang Tua Terhadap Motivasi Belajar Pada Siswa Kelas IV SDN Cibunigeulis 4: - Kusumah, Erlangga; Zulkarnaen, Rizki Hadiwijaya; Mahendra, Hatma Heris (CV. Generasi Insan Rafflesia, 2024)
This research aims to determine the analysis of parenting patterns on learning motivation in fourth grade students at SDN Cibunigeulis 4. The problem in this research is that there are students who lack motivation in studying because of problems in parenting patterns at SDN Bunigeulis 4. Methods in research This method uses a descriptive qualitative method. The data collection techniques used are interviews, documentation and observation. The results of this research are about the analysis of parenting patterns on the learning motivation of grade 4 students at SDN Cibunigeulis 4. There are differences in students' learning motivation in terms of their parents' parenting patterns. Parents who apply a democratic parenting style are better than parents who apply an authoritarian and permissive parenting style. Meanwhile, authoritarian parenting is a category that causes children to be more stressed and spoiled.